تركیا و مشروع الشرق الأوسطي - م.م مازن خلیل إبراھیم م.م محمود عبد الرحمن خلف (College of Education for Women, 2019)
Turkey came back to the Middle East hardly after long disappearance throughout its moderate regional policy, which put its in the middle of the events it reverse its place throughout the regional references in the region, the way of coming back was too difficult and hard, the internal Turkish troubles and inhibitors coming together with the maintenance bonds that forms great complex barrier. But the great Turkish foreign policy represented by the foreign minister Ahmed David Oghlu, can successfully pass these problems and as a result it withdraw turkey both geographical and political to its neighbor after long period of disappear, it new regional policies cancel the old impressions that was still in the mind of the other, especially the old impression that said that either going east or west, this is the old idea in the past that said if you want to go to Europe or west this will delay the bonds or bridge formation with the east. But now Turkish policy leaves the old policies by educational and intellectual way based on political imagination and ambitious thinking doesn't know the impossible. It relay all of that on actual bases reflect deep consciousness in the composition of the region, it achieve its valuable position throughout its regional balance and policies. It seems from the first impression there is certain interaction on its aim for making relationship between the middle east and European union, it's in correct impression for many reasons, one from most important reason because of the new Turkish policies that make it acceptable from many countries from the world and among the world so throughout the Turkish role in the middle east it give insurance to the Europe that it may play the same role in the solving of the middle east troubles this will keep the advantage of the Europe within the region. This will lead that turkey play a central role between the Middle East and Europe, but the reduction of the Turkish foreign policy by choosing between either west or east policy this will make turkey go back to the old historical era, that make it lose its new varieties and sedation. Turkish new policy achieve many success not only just in the security but it achieve new ideological content in contrast to some of the radicals in the past era who refuse the Islamic ottoman history, the justice and development party take its idea and policy from Islamic history of turkey. In spite of that Ankara don't leave the idea for joining the European Union. In addition to that turkey on of the most developed country in the middle east it has affective and modern democratic regime in the region, and productive economy and it discover new balance between the religion and secular so that the security aspect of the middle east will accept and support turkey, it support its goal in control as a big country developed both industrially and civilization ally.